PERBANDINGAN ANTARA INTERVAL TRAINING DENGAN FARTLEK TERHADAP DAYA TAHAN ATLET FUTSAL U-16 RANGGON DALAM LIGA ASSOSIASI AKADEMI FUTSAL INDONESIA 2018 - Iskandar, Tatang (STKIP Pasundan, 2019)
This study aims to determine the effect of Interval Training and Fartlek Methods on fostering endurance. The method used in this research is the experimental method. In this study the authors conducted an experiment in the form of treatment or treatment of two groups of samples in the form of Odd group method Fartlek (A) and Even group training interval (B). In the data collection, the initial test was carried out before being given treatment and the final test to determine the increase in the results of his training The population in this study were Indonesian Futsal League participants from the Jakarta futsal SWAP team, with a total sample of 20 people. Statistical processing and data analysis concluded that: (1) the Fartlek method has a significant influence on increasing endurance through statistical calculations obtained by tcount = 4.1 which is greater than t table = 2.26 at the significance level ? = 0.05 and dk = 9. ( 2) Interval training method has a significant influence on increasing endurance through statistical calculations obtained tcount = 6.63 which is greater than t table = 2.26 at the significance level ? = 0.05 and dk = 9. (3) Fartlek Method and Interval Training are the same -sama provide an increase in endurance for futsal athletes but not significantly obtained tcount = 1.5 which is smaller than t table = 2.10 at significance level ? = 0.05 and dk = 18.